2020
DOI: 10.1038/s41418-020-00698-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender biased neuroprotective effect of Transferrin Receptor 2 deletion in multiple models of Parkinson’s disease

Abstract: Alterations in the metabolism of iron and its accumulation in the substantia nigra pars compacta accompany the pathogenesis of Parkinson’s disease (PD). Changes in iron homeostasis also occur during aging, which constitutes a PD major risk factor. As such, mitigation of iron overload via chelation strategies has been considered a plausible disease modifying approach. Iron chelation, however, is imperfect because of general undesired side effects and lack of specificity; more effective approaches would rely on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…TFR2 β -KI (lacking TFR2 β mouse model) hearts have showed an increased ferritin heavy chain and a decreased FPN1, while LCKO-KI (selective inactivation of liver TFR2 α in KI mice) hearts have presented an upregulation of ferritin-L chain and DMT1/hepcidin-RNA [ 112 ]. Another central nerve study indicated that TFR2 β deletion exerts neuroprotection against dopaminergic degeneration and against Parkinson's disease- and aging-related iron overload [ 113 ]. However, the efficacy of the regulation of TFR2 β on the CIRI remains unclear; further research should be carried out.…”
Section: Ferroptosis In Cirimentioning
confidence: 99%
“…TFR2 β -KI (lacking TFR2 β mouse model) hearts have showed an increased ferritin heavy chain and a decreased FPN1, while LCKO-KI (selective inactivation of liver TFR2 α in KI mice) hearts have presented an upregulation of ferritin-L chain and DMT1/hepcidin-RNA [ 112 ]. Another central nerve study indicated that TFR2 β deletion exerts neuroprotection against dopaminergic degeneration and against Parkinson's disease- and aging-related iron overload [ 113 ]. However, the efficacy of the regulation of TFR2 β on the CIRI remains unclear; further research should be carried out.…”
Section: Ferroptosis In Cirimentioning
confidence: 99%
“…Therefore, a clearer understanding of mechanizing driving PD progression would be beneficial for the proposal of therapeutic approach. A variety of molecular mechanisms that likely contribute to neuronal cell death have been described previously, including α-synuclein aggregation, mitochondrial dysfunction and noxious oxidant stress ( Milanese et al, 2021 ). In addition, neuroinflammation is one of the hallmarks of PD and may induce the degeneration of midbrain dopamine neurons ( Krashia et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…To further enhance its brain targeting property, Aca-LCL was installed with surface-bound transferrin (Tf) to form Tf-Aca-LCL, which was shown to have an improved affinity to the transferrin receptor (TfR) on the surface of nigral dopaminergic neurons ( Fig. 6 B–D) 35 . To address whether Tf-Aca-LCL was BBB-penetrable, a fluorescent agent called IR780 {2-[2-[2-chloro-3-[(1,3-dihydro-3,3-dimethyl-1-propyl- 2H -indol-2-ylidene)ethylidene]-1-cyclohexen-1-yl]ethenyl]-3,3-dimethyl-1-propylindolium iodide} was encapsulated along with acalitide to afford Tf-Aca-LCL-IR780 ( Fig.…”
Section: Resultsmentioning
confidence: 99%